USES OF VARIOUS PREBIOTICS & PROBIOTICS ON GROWTH PERFORMANCE OF BROILERS - RAUF , U; KHAN , A; KHAN , A; IMRAN , M; AHMAD , M; SHAMS , MA; SAHIN , T; KHAN , MJ; ALI , HMM; RAHMAN , HMS (Biological and Clinical Sciences Research Journal, 2024)
Prebiotics and probiotics have been increasingly recognized for their beneficial effects on broiler growth and gut health. As alternatives to antibiotics, these dietary supplements could significantly enhance sustainable poultry production by improving overall health and performance metrics. Objective: This study aimed to evaluate the effects of different prebiotics, probiotics, and their combinations (synbiotics) on broiler growth performance and to assess their potential as antibiotic alternatives. Methods: The 42-day growth trial, a significant undertaking, was conducted with 200 one-day-old Ross 308 broiler chicks, which were randomly allocated into four groups: control (basal diet), prebiotic (0.1% inulin), probiotic (0.1% Lactobacillus and Bifidobacterium mix), and synbiotic (0.1% inulin + 0.1% probiotic mix). The study assessed parametric performance, including body weight gain (BWG) and feed conversion ratio (FCR), blood parameters, and carcass traits as indicative health measures. Statistical analysis was performed using one-way ANOVA to compare group performances, with significance at p < 0.05. Results: The findings indicated that supplementation with prebiotics, probiotics, and especially synbiotics led to a significant increase in body weight gain and improved feed conversion ratio in the supplemented groups, impressively outperforming the control group. The synbiotic group exhibited the best overall potential and feed efficiency. Improvements were also observed in carcass quality and health indicators across all supplemented groups. Conclusion: The study underscored the beneficial impacts of dietary prebiotics, probiotics, and synbiotics on broiler growth performance. These supplements demonstrated considerable potential as sustainable alternatives to antibiotics in poultry diets, enhancing growth performance and overall health.